Accuracy Analysis of a 3D Scanner on Small Dimension Object - Ahmad Puaat, Zainal Mukhriz; Ismail, Muammar Mukhsin; Ishak, Izuan Amin (Progress in Engineering Application and Technology, 2025)
This thesis will research the precision of the GOM II ATOS Triple Scan 3D scanner in capturing dimensional measurements of small-sized objects in metal. The work compares digital measurements from a 3D scanner against conventional measurements using Vernier calipers. Three pieces of metal blocks in various sizes (small, medium, and large) were considered, each scanned five times for reliability. These involve critical procedures of developer spray, placement of reference stickers, and the use of the ATOS Professional V8 software in scanning and post-processing. Some key findings that will be discussed include mean dimensions, absolute errors, and percentage errors per each block size. Consistent deviation is observed in all 3D scanned measurements in relation to manual readings, which indicates that the percentage error has been ranging for all block sizes. Result show the medium block has had the biggest error of compared to other block sizes. Besides, deviations were quantified with the use of RMSE, showing a great importance of good calibration, proper surface preparation, and environmental controls. It confirms the utility of the GOM ATOS II Triple Scan for engineering applications but it detects its limits too, therefore, the following suggestions on its better using in precision tasks are quite valid. This research gives valuable contributions to metrology by identifying and analyzing those factors that influence the reliability of 3D scanning technologies.